2021
DOI: 10.1111/ajt.16772
|View full text |Cite
|
Sign up to set email alerts
|

Properties of regulatory B cells regulating B cell targets

Abstract: Regulatory B cells (Bregs) have shown promise as anti‐rejection therapy applied to organ transplantation. However, less is known about their effect on other B cell populations that are involved in chronic graft rejection. We recently uncovered that naïve B cells, stimulated by TLR ligand agonists, converted into B cells with regulatory properties (Bregs‐TLR) that prevented allograft rejection. Here, we examine the granular phenotype and regulatory properties of Breg‐TLR cells suppressing B cells. Cocultures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The effort to characterize the molecular and biochemical mechanisms by which the regulatory subset of suppressive B cells was not made until the turn of the 21st century when three studies showed that B cells could suppress inflammation through IL-10 production in murine models of colitis, encephalomyelitis (EAE), and arthritis ( 2 , 3 , 14 ). These findings were extended to transplantation models with the observation that B cells were required to develop transplantation tolerance induced by antibody treatments ( 7 , 15 17 ). Studies on genetically modified B cells and B cells from IL-10-deficient mice showed that defective Breg differentiation and function causes chronic inflammation ( 14 ).…”
Section: Breg Differentiation Function and Cytokine Productionmentioning
confidence: 93%
See 2 more Smart Citations
“…The effort to characterize the molecular and biochemical mechanisms by which the regulatory subset of suppressive B cells was not made until the turn of the 21st century when three studies showed that B cells could suppress inflammation through IL-10 production in murine models of colitis, encephalomyelitis (EAE), and arthritis ( 2 , 3 , 14 ). These findings were extended to transplantation models with the observation that B cells were required to develop transplantation tolerance induced by antibody treatments ( 7 , 15 17 ). Studies on genetically modified B cells and B cells from IL-10-deficient mice showed that defective Breg differentiation and function causes chronic inflammation ( 14 ).…”
Section: Breg Differentiation Function and Cytokine Productionmentioning
confidence: 93%
“…Studies on genetically modified B cells and B cells from IL-10-deficient mice showed that defective Breg differentiation and function causes chronic inflammation ( 14 ). Bregs promote immunological tolerance through suppression of T cell expansion, downregulation of the production of pro-inflammatory cytokines, and maintenance of immune homeostasis through the synthesis of immune modulating cytokines TGF-β, IL-35, and IL-10 and by promotion of regulatory T cells (Tregs) ( 7 , 14 , 16 , 18 ).…”
Section: Breg Differentiation Function and Cytokine Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, donor-specific Bregs-TLR are more efficient at promoting graft survival, suggesting that local targeting via the Bcell receptor may play a role in specific homing of the regulatory cells to the graft. 11 A recent study from the same group further showed that Bregs-TLR can inhibit cognate Bcell activation, proliferation, and development into plasma cells. It was hypothesized that because Bregs-TLR express very high levels of major histocompatibility complex class II, they may induce CD4+ T cell anergy by presenting relevant antigens in a tolerogenic milieu.…”
mentioning
confidence: 99%
“…The group further focused on characterizing subsets of Breg‐TLR cells through single‐cell RNA sequencing, showing that B cells stimulated through the TLR‐9 and TLR‐4 pathways have a unique expression profile, characterized by high expression of TGFβ. Interestingly, donor‐specific Bregs‐TLR are more efficient at promoting graft survival, suggesting that local targeting via the Bcell receptor may play a role in specific homing of the regulatory cells to the graft 11 . A recent study from the same group further showed that Bregs‐TLR can inhibit cognate Bcell activation, proliferation, and development into plasma cells.…”
mentioning
confidence: 99%